KESULITAN BELAJAR ANAK USIA SEKOLAH DASAR - Aulia, Lailatuzzahro Al-Akhda (Fakultas Psikologi Universitas Yudharta Pasuruan, 2018)
Learning difficulties are a problem that can arise anywhere and can be experienced by anyone. Learning difficulties are not always caused by low intelligence factors, but can also be caused by non-intelligence factors. Parenting has contributes to the development of children, including his personality and also in the learning process. This study was conducted to determine the causes of learning difficulties experienced of school-aged children. Method used qualitative research, with eskplanatoris case study. Subjects in this study is a school-aged children were 10 year old. Data gathered in this research is by using interview, observation, intelligence test (CFIT test), and graphic test. The results showed that learning difficulties experienced by subjects other than due to intelligence factors, also influenced by the parenting has received by the subject in the family